Diabetes : what to eat. - Meredith Corporation (Hoboken, N.J. : Wiley, 2011)
'The essential cookbook and everyday guide on what to eat when you have diabetesDiabetic Living{u0B61}gazine's trustworthy resource for anyone living with diabetes gives over 200 recipes and essential advice on what to eat in order to control blood sugar, feel better, and enjoy delicious meals every day. Enjoy carb-smart recipes like Beef Fajitas, Panko-Crusted Chicken, Speedy Pizza Bites, and Layered Brownies. In addition, you'll find the information every newly diagnosed individual needs to know to eat right--from how to shop for groceries and read food labels to counting carbs--all clearly explained in the magazine's friendly, approachable style. Features include: Chapters covering breakfast, salads, soups, sandwiches, main dishes and slow-cooker suppers, desserts, snacks, and drinks More than 200 beautiful full-color photographs A complete intro chapter on controlling blood sugar, counting carbs, navigating the grocery store, stocking your pantry, and more Full nutrition information and highlighted carb counts provided for every recipe'--Provided by publisher.
'Diabetic Living magazine's ultimate, trustworthy resource for those newly diagnosed with diabetes tells you what to eat, with over 200 mouthwatering recipes accompanied by the essential, practical information you need to take control and eat right every day'--Provided by publisher.
'Your complete guide to eating what you love'--Cover.
'A Better Homes and Gardens book'--Cover.
Includes index.
Keywords: Diabetes -- Diet therapy; Cookbooks